Analisis Penerapan Total Quallity Management (TQM) Dalam Upaya Meningkatkan Kepuasan Pelanggan Pada Hotel Yonnas di Kota Teluk Dalam Kabupaten Nias Selatan - Risdayani Daya; Eduar Baene; Jeliswan Berkat Iman Jaya Gea; Fatolosa Hulu (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2024)
This research analyzes the application of total quality management (TQM) in an effort to increase customer satisfaction at the Yonnas Hotel in Teluk Dalam City, South Nias Regency. Hotels are a service industry that includes lodging, food and beverage services, travel agencies and others, the hotel industry operates in the service sector This accommodation is also the same as other industries. Where it is growing and there are more and more hotel buildings in every place. Both in big cities and small towns. The main function of the hotel industry is as a temporary residence for guests who generally go on long trips, or carry out special and general activities and can also be a place for tourists who want to go on holiday, and can also be a place for meetings, gatherings, birthday events. , as well as wedding events. The aim of this research is to determine the application of total quality management (TQM) in an effort to increase customer satisfaction at the Yonnas Hotel in Teluk Dalam City, South Nias Regency. This research uses qualitative research methods using data collection, data reduction and documentation techniques. The data analysis techniques are data collection, data reduction, data presentation and conclusion drawing. The sources of informants for this research are the leaders (owners) of the Yonnas Hotel, general managers, employees and customers/guests of the Yonnas Hotel. The results of this research show that implementing TQM can increase customer satisfaction if it is fully implemented or implemented. Where TQM refers to organizational change, starting from changes in structure, goals, leadership and the role of employees in achieving a goal. Total Quality Management (TQM) in an effort to increase customer satisfaction can also achieve total business excellence and competitiveness. Because customer satisfaction is the level of customer satisfaction after receiving the services provided by a business. Therefore, with the main elements in TQM that can be used as a reference in increasing customer satisfaction, namely focus on customers, obsession with quality, scientific approach, long-term commitment, teamwork, continuous system improvement, education and training, controlled freedom, unity of purpose, employee involvement and empowerment. If the TQM elements are fully implemented or implemented within the Yonnas Hotel, it can increase customer satisfaction effectively and efficiently.